Andean Speciation and Vicariance in Neotropical Macrocarpaea (Gentianaceae-Helieae) - Struwe, Lena; Haag, Scott; Heiberg, Einar; Grant, Jason (My University, 2009)
The genus Macrocarpaea (Griseb.) Gilg (Gentianaceae, Helieae) is among the largest woody genera of tropical gentians, with most of its species occurring in the wet mountainous forests of the Andes. Phylogenetic and dispersal-vicariance analyses (DIVA) of 57 of the 105 currently recognized species in the genus, using two data sets from nuclear DNA (ITS and 5S-NTS sequences) and morphology, show a single origin of the Andean species from an ancestral distribution that includes southeastern Brazil. Within the Andes, species divide into two major clades: (1) northern species from the cordilleras of northern Ecuador, Colombia, and Venezuela; and (2) southern species of the Andean Amotape–Huancabamba Zone in Ecuador and Peru, as well as the Andes of central and southern Peru and Bolivia. The Amotape–Huancabamba Zone is supported as the ancestral area for Macrocarpaea within the Andes. There are repeated speciation patterns within the Andes, and three Mesoamerican species derive from the northern clade, as is the single sampled species from the Guayana Shield. The position of the subclade of the three Caribbean species is less certain, but it currently nests among Andean species. An Atlantic coastal Brazilian clade is placed as sister group to all other Macrocarpaea, providing further support for an ancestral refuge in southeastern Brazil for the Helieae. The biogeographic analysis showed that local speciation is more common than long-distance dispersal, and allopatric speciation is more common than sympatric speciation. Using detailed, georeferenced herbarium collection data, patterns in environmental characteristics between clades and sister species were analyzed with Spatial Evolutionary and Ecological Vicariance Analysis (SEEVA), utilizing geographic information system (GIS) and statistical methods. Sister clades and taxa were evaluated for statistical significance in variables such as annual rainfall and temperature, elevation, temperature and rainfall seasonality, geological bedrock age, and soil type to evaluate ecological vicariance between sister groups. The results indicate that there are no general patterns for each variable, but that there are many significant divergences in ecological niches between both larger sister groups and sister species, and ecological niche conservation was also observed when subsequent nodes in the phylogeny were compared.
Keywords: Biogeography; ecology; Gentianaceae; Macrocarpaea; Neotropics; niche; South America; speciation; vicariance